KARAKTER DAN TIPE MINERALISASI HIDROTERMAL DI WILAYAH BOMBANA BERDASARKAN STUDI MINERALOGI DAN GEOKIMIA - Setiawan, I.; Indarto, S.; Ismiyanto, AF.; Sudarsono, Sudarsono (Pusat Survei Geologi, 2012)
Bombana gold mineralization occurs within metamorphic rocks hosted environment, and it's not yet reported having connection with magmatisme/volcanisme. Therefore most ore mineral deposits have to be related with volcanisme bearing metallic mineralization. The aim of this study is to explain the character and types of gold deposit using petrography, mineragraphy, fluid inclusions, AAS, and geochemistry methods.Bombana area formed by orogenic activities which is composed by metamorphic rocks mainly consists by greenschist facies and ultra mafic rocks. Petrographically rocks called as garnet glaukofane amphibol schist, peridotite, serpentinite, sandstone meta, limestone meta, andesite meta, and altered rocks. While based on major elements composition, their parent rocks has ultrabasic-acidic rocks composition, formed peridotite to andesite.Gold mineralization of Bombana area indicates an epithermal-mesothermal type, which is exhibited by hydrothermal evidences such as crosscut veins after foliation and alteration at vicinity of quartz/calcite veins. These indicate that mineralization resulted by hydrothermally process and formed after metamorphism. Ore minerals consisted of gold, pyrite, chalcopyrite, goethite, lepidocrocite and cinabar and commonly associated with quartz veins as mineralized fluids suggested as low salinity (0,18-1,78)% NaCl equivalent and water rich mineralized fluid, at (210-350)ºC temperatur ranges.Keywords: Bombana, volcanic rocks, epithermal, metamorphism